Poetics, politics and protest in Arab theatre : the bitter cup and the holy rain - Ḥamdān, Masʻūd (Brighton [England] ; Portland, Or. : Sussex Academic Press, 2006)
Writing from a socio-historical point of view, the author surveys and discusses the popular theatrical phenomena in the Arab world from the Hellenic period to the beginning of the 21st century. He notes the Eastern carnivalesque folk sources and the tendency toward comedy rather than tragedy.
1. Theatrical genres and the carnivalesque : art of the theatre -- 2. Theatre in the Arab World : the historical background -- 3. The early comedies of Durayd Lahham and Nihad Qal'i : birth pangs of late satire -- 4. When a gay rogue grows to be a tragic fool : the carnivalesque satires.
P.B
P.B
Includes bibliographical references (pages 172-183) and index.
Keywords: Arabic drama -- Syria -- History and criticism; Political plays, Arabic -- Syria -- History and criticism; Théâtre syrien -- Histoire et critique; Arabic drama; Political plays, Arabic; Politisches Theater; Toneel; Politieke aspecten; Syria; Syrien; Midden-Oosten.; Arabisch; Geschichte 1974-1993; Criticism, interpretation, etc